ANALISIS PROYEKSI ARUS KAS DAN KINERJA KEUANGAN PT.ADHI KARYA (PERSERO) TBK SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTOR - Sekar Ratri Ayuningrum; Gatut Dradjad Purwoko (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the financial performance and cash flow projections of PT Adhi Karya (Persero) Tbk as a basis for investor decision-making. Financial performance is analyzed through liquidity and profitability ratios for the 2015-2024 period, while cash flow projections are compiled based on historical cash flow data and the results of the company's financial performance analysis. This study uses a quantitative research method with a descriptive approach. The data used are secondary data sourced from the annual financial statements of PT Adhi Karya (Persero) Tbk for the 2015-2024 period. The results show that the financial performance of PT Adhi Karya (Persero) Tbk during the study period fluctuated. The liquidity ratio tends to be in the unhealthy category due to high short-term liabilities, while the profitability ratio showed a significant decline in 2020 and began to recover in the following period, although not yet fully stable by industry standards. The prepared cash flow projections indicate that the company's ability to generate cash flow is still affected by suboptimal liquidity and profitability conditions. Overall, the results of the financial performance analysis and cash flow projections can be used as a basis for consideration for investors in making investment decisions, taking into account the level of risk, financial stability, and the company's future cash flow prospects. Keywords: Cash Flow Projection, Financial Performance, Liquidity Ratio, Profitability Ratio, Investor Decision, PT Adhi Karya (Persero) Tbk.